2021
DOI: 10.3389/fncel.2021.629279
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Induced Microglia-Like Cells (iMG Cells) for Future Studies of Brain Diseases

Abstract: Microglia are the primary resident immune cells of the central nervous system that maintain physiological homeostasis in the brain and contribute to the pathogenesis of many psychiatric disorders and neurodegenerative diseases. Due to the lack of appropriate human cellular models, it is difficult to study the basic pathophysiological processes linking microglia to brain diseases. In this study, we adopted a microglia-like cellular model derived from peripheral blood monocytes with granulocyte-macrophage colony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…A gene ontology enrichment analysis performed for each of these groups revealed that only the master TFs retrieved on all of the protocols (first group) or those retrieved on protocols other than that using specific TFs-overexpression (second group) are significantly enriched for microglia-related terms (Figure 4B). This microglia-related TFs enrichment is also supported by a comparison with master players retrieved in three other studies, either issued from in vivo microglia collected from surgically resected brain tissue [39], from matured microglia due to their co-culturing with human neuronal precursors [41], or differentiated from peripheral monocytes [40] (Supplementary Figure S4). as well as those related to the fetal and adult microglia control datasets (Figure 4D).…”
Section: A Master Tf Co-regulatory Network Driving Microglia Differentiation Reveal Strengths and Weaknesses Of The Compared Protocolssupporting
confidence: 71%
See 2 more Smart Citations
“…A gene ontology enrichment analysis performed for each of these groups revealed that only the master TFs retrieved on all of the protocols (first group) or those retrieved on protocols other than that using specific TFs-overexpression (second group) are significantly enriched for microglia-related terms (Figure 4B). This microglia-related TFs enrichment is also supported by a comparison with master players retrieved in three other studies, either issued from in vivo microglia collected from surgically resected brain tissue [39], from matured microglia due to their co-culturing with human neuronal precursors [41], or differentiated from peripheral monocytes [40] (Supplementary Figure S4). as well as those related to the fetal and adult microglia control datasets (Figure 4D).…”
Section: A Master Tf Co-regulatory Network Driving Microglia Differentiation Reveal Strengths and Weaknesses Of The Compared Protocolssupporting
confidence: 71%
“…Inferred consensus master transcription factors were compared with master players described in three further studies: Gosselin et al [39], which was based on in vivo microglia isolated from surgically resected brain tissue and that had been cultured in an in vitro environment; Banerjee et al [40], who described a protocol for iMGL generation from peripheral monocyte samples; and Grubman et al [41], who described an enhanced maturation of iMGL precursors when co-cultured with human neuronal precursors (ReN) (Supplementary Figure S4). Specifically, the raw read counts provided by Grubman et al (GSE125872) were used to query for genes being over-expressed in the iMG + ReN conditions relative to their corresponding iPSC sample.…”
Section: Reconstruction Of Gene Co-regulatory Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research groups and ours have revealed that iMG cells express microgliaspecific surface markers (CX3CR1, P2RY12, TMEM119, and others) and possess phagocytic activity (22,25,26). Recently, iMG cells have been reported to be distinct from monocytes and macrophages but clustered closer with human brain microglia [Ohgidani 2020 under review] (25). These results suggest that iMG cells are a promising research tool for less-invasive monitoring of the immunological state of microglia in the CNS.…”
Section: Introductionmentioning
confidence: 60%
“…We applied this technique for translational research focusing on neurological, psychiatric, and pain-related disorders (23,24). Other research groups and ours have revealed that iMG cells express microgliaspecific surface markers (CX3CR1, P2RY12, TMEM119, and others) and possess phagocytic activity (22,25,26). Recently, iMG cells have been reported to be distinct from monocytes and macrophages but clustered closer with human brain microglia [Ohgidani 2020 under review] (25).…”
Section: Introductionmentioning
confidence: 99%